KONSEP SABAR DALAM TAFSIR ḤAQĀ’IQ AL-TAFSĪR KARYA AL-SULAMĪ: ANALISIS TAFSIR SUFISTIK ATAS KISAH NABI AYYŪB A.S. - Syu'ban Aziz; Izzah Faizah Siti Rusydati Khaerani; Asep Faturahman (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2025)
This study analyzes the meaning and dimensions of patience in the story of the Prophet Ayyūb a.s. as interpreted in Ḥaqā’iq al-Tafsīr by Abū ‘Abd al-Raḥmān al-Sulamī. It seeks to reveal the meaning of patience from a Sufi perspective and analyze it through the framework of self-control theory proposed by James Averill (1973). This study employs a qualitative, library-based research approach. Content analysis is the primary analytical method used to examine Al-Sulamī's interpretation of Prophet Ayyūb a.s. The data are analyzed using Averill's three-part theory of self-control (behavioral, cognitive, and decisional). According to this study, Al-Sulamī viewed Ayyūb a.s's patience as an active spiritual practice, not just passive endurance. Its key dimensions include steadfast dhikr (remembrance of God) to manage suffering, merging the self (fanā) with the divine will and grace, and a pinnacle of patience manifested as tawakkal (complete surrender). According to Averill's psychological framework, these dimensions demonstrate behavioral control (restraining the body from complaining), cognitive control (reinterpreting hardship as divine will), and decisional control (a conscious choice to surrender to God). This analysis reveals the implicit psychological messages in the story. This study found that the story contains a sophisticated psychological model for resilience. It refutes the notion of patience as passive behavior, demonstrating that it is an active spiritual and psychological process. This study's novelty stems from its interdisciplinary approach, which bridges 10th-century classical interpretation with 20th-century psychological theory while also providing new insights into the psychological depth of Islamic spiritual concepts. Penelitian ini bertujuan untuk menganalisis makna dan dimensi kesabaran Nabi Ayyūb a.s. dalam Ḥaqā’iq al-Tafsīr  karya Abū ‘Abd al-Raḥmān al-Sulamī. Kesabaran tersebut dianalisis dengan teori self-control James Averill (1973). Penelitian ini berjenis kualitatif, menggunakan metode analisis isi dengan pendekatan studi kepustakaan (library research). Data tersebut diinterpretasi oleh teori tripartit self-control (perilaku, kognitif, dan keputusan) Averill. Studi ini menemukan bahwa Al-Sulamī menafsirkan kesabaran Ayyūb a.s. bukan sebagai ketahanan pasif, melainkan sebagai praktik spiritual yang aktif dan kompleks. Dimensi-dimensi kuncinya meliputi: keteguhan hati, menjadikan zikir (mengingat Allah) untuk mengendalikan penderitaan, meleburkan diri (fanā) dengan kehendak—anugerah-- Allah, dan puncak kesabarannya diwujudkan dengan tawakal (kepasrahan mutlak). Dimensi-dimensi dalam kerangka psikologi Averill menunjukan kontrol perilaku (menahan tubuh dari keluhan), kontrol kognitif (menafsirkan ulang kesulitan sebagai kehendak Ilahi), dan kontrol keputusan (pilihan sadar untuk berserah diri kepada Tuhan), Tiga aspek ini merupakan pesan utama dari kisah Nabi Ayyūb a.s. Penelitian berhasil bentuk psikologis yang canggih untuk resiliensi. Sekaligus menentang bahwa kesabaran sebagai perilaku pasif, namun proses psikologis yang aktif. Kebaruan penelitian ini terletak pada pendekatan interdisipliner yang menghubungkan tafsir sufistik klasik abad ke-10 dengan teori psikologi modern, sehingga memperkaya pemahaman terhadap dimensi psikologis dalam konsep spiritual Islam.